New rural finance institutions in Sierra Leone - Gbakie, Emmanuel Sahr; Kamara, Brima; Dumbuya, Patrick A.F. (Technical Centre for Agricultural and Rural Cooperation, 2018)
Working to eradicate rural poverty and promote economic growth, the Government of Sierra Leone, with financial support from the International Fund for Agricultural Development, has established 17 rural finance institutions across the country. With the widest financial network in the country, community banks are providing access to saving and loan facilities for increasing numbers of rural people.